POLA DEMOKRASI YANG DIKEMBANGKAN PENDIRI BANGSA - Hariyono, Hariyono (Paramita: Historical Studies Journal, 2012)
The founding fathers have concerned with democracy since the early struggle of nation independence. They have considered that Indonesian people could not develop their justice and prosperity without democracy. Colonialism and feodalism had influenced mentality and character of Indonesian people as an inferior personality. Considering those situation, the founding fathers attempted to develop a daily democratic system which is practiced in government system. In general, there are two existing models of democracy which is developing, that are, the cultural democracy and the radical democracy. The cultural democracy model tends to develop as a gradual process and their supporters could cooperate with the colonial government. On the contrary, the radical democracy model assumed that democracy, included economic and political aspects and also their supporter, could not cooperate with the colonial government. Keywords: The Founding FatherÃ¢â¬â¢s, cultural democracy and radical democracy. ÃÂ  Para pendiri bangsa telah peduli dengan demokrasi sejak perjuangn awal kemerdekaan bangsa. Mereka menganggap bahwa orang Indonesia tidak bisa berkembang menuju keadilan dan kesejahteraan tanpa demokrasi. Kolonialisme dan feodalisme telah mempengaruhi mentalitas dan karakter bangsa Indonesia sebagai pribadi yang rendah. Melihat situasi tersebut para pendiri bangsa berusaha mengembangkan sistem demokrasi dalam kehidupan sehari-hari yang dipraktikkan dalam sistem pemerintah. Secara umum, model demokrasi yang berkembang dapat dibedakan dalam dua model, yang merupakan demokrasi budaya dan demokrasi radikal. Model demokrasi budaya cenderung berkembang sebagai rangkaian proses bertahap dan pendukungnya bisa kerjasama dengan pemerintah kolonial. Sebaliknya, model demokrasi radikal berasumsi bahwa demokrasi termasuk baik aspek ekonomi dan politik dan kerjasama pendukungnya tidak bisa dengan pemerintah kolonial. Kata kunci: pendiri bangsa, demokrasi kulrural, demokrasi radikal. ÃÂ